Festival Personality and How It Influences Visitor Attitude and Intention - Quintal, Vanessa; Lwin, Michael; Phau, Ian; Sood, Abhinav (2020)
This study explores festival personality for its impacts on visitor attitude and intention toward festivals. Two distinct and popular festivals held at a botanic park in Western Australia were selected for the research. A total of 481 local and international visitors participated in the self-administered, pen-and-paper and online surveys. The Excitement personality attribute was unique to the Chili Festival, whereas the Cheerfulness personality attribute was unique to the Tulip Festival. Both festivals embodied the Imagination personality attribute, suggesting the place in which a festival is held may embody its own attributes, which contribute to the holistic personality of the festival. For both festivals, the personality attributes had significant impact on favorable visitor attitude, resulting in their positive intention toward these festivals. The study paves the way for researchers to extend brand personality research to the event tourism domain, particularly in the niche sector of festivals. The enhanced understanding lends input into how festival organizers, brand managers, and marketers can manage the positioning, differentiation, and communication strategies of their festivals in this competitive sector.